Storage stability and degradation kinetics of bioactive compounds in red palm oil microcapsules produced with solution-enhanced dispersion by supercritical carbon dioxide: a comparison with the spray-drying method - Lee, Wan Jun; Tan, Chin Ping; Sulaiman, Rabiha; Hee, Yen Yi; Chong, Gun Hean (Elsevier BV, 2020)
Solution-enhanced dispersion by supercritical carbon dioxide (SEDS) and spray drying (SD) were used to microencapsulate red palm oil (RPO) to prolong the functionality of carotenes and vitamin E. The protective effects provided by SEDS and SD were evaluated in terms of the oxidative stability (65 °C for 35 days), fatty acid compositions, color change and degradation kinetics of carotenes and vitamin E (25 °C, 45 °C, 65 °C, and 85 °C for up to 198 days). SEDS microcapsules (SEDS-M) were the most oxidatively stable (total oxidation (Totox): 26.5), followed by SD microcapsules (SD-M) (34.9) and RPO (56.7). Degradation of carotenes and vitamin E fitted well a first-order kinetic model (average absolute relative deviation = 2–16%). SEDS-M offered better protection to vitamin E (Ea = 36 kJ/mol), whereas SD-M provided better protection for α + β carotene (Ea = 29 kJ/mol). Overall, encapsulation protected RPO during storage, with SEDS-microencapsulated RPO performing better than SD-microencapsulated RPO.